Intermittent theta burst over M1 may increase peak power of a Wingate anaerobic test and prevent the reduction of voluntary activation measured with transcranial magnetic stimulation - Louis-Solal Giboin; Patrick Thumm; Raphael Bertschinger; Markus Gruber (Frontiers in Behavioral Neuroscience, 2016)
Despite the potential of repetitive transcranial magnetic stimulation (rTMS) to improve performances in patients suffering from motor neuronal afflictions, its effect on motor performance enhancement in healthy subjects during a specific sport task is still unknown. We hypothesised that after an intermittent theta burst (iTBS) treatment, performance during the Wingate Anaerobic Test (WAnT), will increase and supraspinal fatigue following the exercise will be lower in comparison to a control treatment.Ten subjects participated in two randomised experiments consisting of a WAnT 5 minutes after either an iTBS or a control treatment. We determined voluntary activation (VA) of the right knee extensors with TMS (VATMS) and with peripheral nerve stimulation (VAPNS) of the femoral nerve, before and after the WAnT. T-tests were applied to the WAnT results and a 2 way within subject ANOVA was applied to VA results. The iTBS treatment increased the peak power and the maximum pedalling cadence and suppressed the reduction of VATMS following the WAnT compared to the control treatment. No behavioural changes related to fatigue (mean power and fatigue index) were observed.These results indicate for the first time that iTBS could be used as a potential intervention to improve anaerobic performance in a sport specific task.